Auditoría De Gestión Y Su Incidencia En Los Procesos Operativos Del Departamento De Talento Humano Del Gad Municipal Del Cantón Valencia, Año 2022–2023 - Millingalle Chinguercela, Dorian David (2025)
The management of the Human Talent Department of the Municipal GAD of the Canton of Valencia during the years 2022 and 2023 showed weaknesses in its operational processes, a situation that prompted the execution of a performance audit and its impact on operational processes. The audit aimed to analyze the degree of regulatory compliance, the implementation of recommendations issued in previous audits, and, through internal control based on COSO I, the application of performance indicators. The research was conducted using a descriptive and exploratory methodological approach, applying inductive and deductive methods and techniques such as interviews and document review. The sample consisted of five public servants from the department. The results revealed that regulatory compliance reached a general level of 80%. It was verified that 85.71% of the previous recommendations were adequately implemented, while 14.29% showed partial progress. Internal control showed a confidence level of 73% and a risk level of 27%. Complemented by graphical analysis of cause-effect indicators, factors negatively affecting efficiency were identified, such as the absence of a structured performance evaluation system and limited implementation of corrective actions. Regarding indicators, efficiency was reported at 0% and effectiveness at 50%, with low levels of training and job satisfaction. These findings, supported by graphs and evaluation matrices, demonstrated limited follow-up on human talent management. The performance audit enabled the formulation of recommendations for improving operational processes and strengthening institutional capacity.